Analisis Lembaga Keuangan Simpanan (LPS) di Indonesia - Mei Sarah Andriani Tobing; Putri Salsabila; Feri Sahputra; Hasyim H (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
National banking is entering a new phase, the existence of LPS cannot prevent it from being cut off from efforts to increase financial sector stability to recovery. When a bank goes missing, people trust that their money is safe and the government will pay it back. However, it cannot be denied that there are still many institutions that are not functioning properly. Understanding LPS. This research is normative, meaning that it takes the law as the standard. For book research, namely studying the law as a whole, including issues of statutory regulations from the Basic Law on analytical techniques, the results of the research show that it is the customers who save money from banks. system, protected by law.